K and Cs Doped Ag/Al_2O_3 Catalyst for Selective Catalytic Reduction of NOx by Methane - 하헌필; 라오; 최희락; 유창용 (한국분말야금학회, 2011)
In the present study, potassium and caesium doped Ag/Al_2O_3 catalysts were synthesized by simple wet impregnation method and evaluated for selective catalytic reduction (SCR) of NOx using methane. TEM analysis and diffraction patterns demonstrated the finely dispersed Ag particles. BET surface measurements reveal that the prepared materials have moderate to high surface area and the metal amount found from ICP analysis was well matching with the theoretical loadings. The synthesized K-Ag/Al_2O_3 and Cs-Ag/Al_2O_3 catalysts exhibited a promotional effect on deNOx activity in the presence of SO_2 and H_2O. The long-term isothermal studies at 550°C under oxygen rich condition showed the superior catalytic properties of the both alkali promoted samples. The crucial catalytic properties of materials are attributed to NO adsorption properties detected by the NO TPD.